An Inflammatory Story: Antibodies in Tuberculosis Comorbidities - McLean, Milla R.; Lu, Lenette L.; Kent, Stephen J.; Chung, Amy W. (Frontiers in Immunology, 2019)
Mycobacterium tuberculosis (Mtb) resides in a quarter of the world’s population and is the causative agent for tuberculosis (TB), the most common infectious reason of death in humans today. Although cellular immunity has been firmly established in the control of Mtb, there is growing evidence that antibodies may also modulate the immune response. More specifically, certain antibody features are associated with inflammation and are divergent in different states of human infection and disease. Importantly, TB impacts not just the healthy but also those with chronic conditions. While HIV represents the quintessential co-morbid condition for TB, recent epidemiological evidence shows that additional chronic conditions such as diabetes and kidney disease are rising. In fact, the prevalence of diabetes as a co-morbid TB condition is now higher than that of HIV. These chronic diseases are themselves independently associated with pro-inflammatory immune states that encompass antibody profiles. This review discusses isotypes, subclasses, post-translational modifications and Fc-mediated functions of antibodies in TB infection and in the co-morbid chronic conditions of HIV, diabetes, and kidney diseases. We propose that inflammatory antibody profiles, which are a marker of active TB, may be an important biomarker for detection of TB disease progression within comorbid individuals. We highlight the need for future studies to determine which inflammatory antibody profiles are the consequences of co-morbidities and which may potentially contribute to TB reactivation.